Pengaruh Fungsi Audit Internal dan Fungsi Manajemen Risiko Terhadap Kinerja Perusahaan Pada PT Inkomas Lestari - Muryanti, Sri; Yuwono, Minto (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to determine the impact of the Internal Audit function and the Risk Management function on company performance. This research was conducted at PT Inkomas Lestari and the respondents of this study were from the Internal Supervisory Unit (SPI) and the Finance and Accounting Unit using non probability sampling techniques. Furthermore, the data will be processed with the help of SPSS software version 25.0. The results showed that Internal Audit and Risk Management simultaneously had a positive and significant effect on the Company Performance of PT Inkomas Lestari by 75.4%. The remaining variables affected by 24.6% can be influenced by other variables that are not used but still have a relationship with this study.